Structural and electronic properties of bulk and low-index surfaces of zincblende PtC. (8th February 2017) - Sensoy, Mehmet Gokhan; Toffoli, Daniele; Ustunel, Hande
Abstract: Transition metal carbides have been extensively used in diverse applications over the past decade. Their versatility is in part thanks to their unique bonding, which displays a mixture of ionic, metallic and covalent character. While the bulk structure of zincblende (ZB) PtC has been investigated several times, a detailed understanding of the electronic and structural properties of its low-index surfaces is lacking. In this work, we present an ab initio investigation of the properties of five crystallographic ZB PtC surfaces (Pt/C-terminated PtC(1 0 0), PtC(1 1 0) and Pt/C-terminated PtC(1 1 1)). Upon geometry optimization, both polar and nonpolar surfaces undergo a mild interlayer relaxation, without extensive reconstructions. Calculated vacancy formation energies indicate facile C removal on the (1 1 1) surface while Pt-vacancy formation is endothermic. Finally, atomic O adsorption energies on all surfaces reveal a high affinity of the C-terminated surfaces towards this species.